Attitude towards school science in primary education in Spain - Raquel Fernández Cézar; Natalia Solano Pinto (Universidad Autónoma de Baja California, 2017)
This report shows Spanish elementary school students' attitude towards school science. The analysis is performed through a questionnaire with a sample consisting of 183 10 to 12-year-old students. The association of this attitude with factors like sex, age, school environment and teachers' use of experiments has been researched. The results show a positive attitude towards school science, and null association with sex or age. Besides that, there is an association between school environment and attitude: the students with the most positive attitude values belong to rural schools. A sex bias is observed in the group of students with the most positive attitude, with girls making up the majority. The small size of this reduced sample limits the impact of this conclusion. A difference in the perception of experiments is observed between teachers and students. Attitude towards school science is not associated with students' perception of experiments in science classes.